Anti-periodic solution for fuzzy Cohen–Grossberg neural networks with time-varying and distributed delays - Li, Yongkun; Yang, Li; Wu, Wanqin (Nonlinear Analysis: Modelling and Control, 2015)
In this paper, by using a continuation theorem of coincidence degree theory and a differential inequality, we establish some sufficient conditions ensuring the existence and global exponential stability of anti-periodic solutions for a class of fuzzy Cohen–Grossberg neural networks with time-varying and distributed delays. In addition, we present an illustrative example to show the feasibility of obtained results.